RADICALISM AND PEACE IN THE WOMEN'S WORLD - Chosinawarotin Chosinawarotin (Universitas Islam Balitar, 2018)
The nature of Rahmatan lil alamin stated in the Qur'an is truly tested in the historical arena through the behavior of terrorism under the guise of Islam. The nature of this sacred concept turns into a relative and problematic necessity. Women with basic feminine characters turn fierce when trapped in the role of being a Terrorist. Harm the mother's empathy power which is actually called affection. Various facts and data recorded as social facts are then dissected to voice the potential of the actual role of women as agents of change towards peace.